Learning skills - solutions to problems faced by students - Rahman, Farhana; Jahan, Farjana (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.